(untitled) (Annals of Medical Research, 2021)
Aim: Premature ejaculation is the most common form of male sexual disease observed clinically. In spite of this, the etiologic factors and disease pathophysiology are still not fully understood. This study compares the most frequently observed premature ejaculation forms to investigate the effective predictive factors in the occurrence of this disease.Materials and Methods: The clinical records of a total of 109 patients were retrospectively investigated for two types of premature ejaculation with 64 patients in the lifelong group and 42 patients in the acquired group. The study included demographic data like age, marital status and body mass index (BMI), parameters like metabolic syndrome (metS) components according to the cholesterol study group of blood triglycerides, high density (HDL) cholesterol, and fasting blood sugar and measured testosterone. Additionally, the internationally ejaculation latent time(IELT), premature ejaculation- diagnostic tool (PE-DT), internationally prostate symptom score (IPSS), internationally index of erectile function (IIEF) and premature ejaculation (PE)anxiety scoring forms were included in the study.Results: Among demographic data, there were statistical differences between the ages in the groups (30.6±7.7 vs 44.4±10.1, respectively, p 0.001). Additionally, fasting blood sugar (FBS), triglyceride, HDL cholesterol and testosterone values were statistically different between the groups (p0.001) and these values were worse in the acquired PE group. Hypertension rates were higher in the acquired PE group compared to the lifelong PE group (9 (21.4%) vs 5 (7.8%), p0.001). The IIEF score was lower in the acquired PE group (p0.001). Logistic regression analysis found age and FBS were independent predictive factors [Odds ratio (ODs); 1.144 and 1.044, respectively]. ROC analysis found the cut-off points and AUC values for age and FBS were 36.5 yearsand0.856 and 102.5 gr/dl and 0.746, respectively.Conclusion: The association of metS components, LUTS and acquired PE was constant. In light of these findings, different from lifelong PE, there is benefit to orienting toward the causes of this disease primarily for treatment of acquired PE.